Laparoscopic resection is not superior to endoscopic resection for relative small gastric gastrointestinal stromal tumors: A propensity score-matched study - Li, De-Liang; Zhou, Yang-Yang; Zhang, Ji-Yu; Liu, Dan; Zhao, Li-Xia; Liu, Bing-Rong (Frontiers in Oncology, 2022)
Background and Aim: Endoscopic resection (ER) and laparoscopic resection (LAP) have been recommended for the treatment of gastric gastrointestinal stromal tumors (GISTs) less than 2cm. However, the therapeutic approach for gastric GISTs between 2-5 cm in diameter is still under debate. In this retrospective study, we aimed to evaluate the feasibility, efficacy and safety of ER for gastric GISTs (2-5 cm), compared with LAP. Methods: From January 2011 to January 2018, 197 patients GISTs at our institution with tumor diameter between were included in our study. Clinical baseline characteristics, histopathological results, perioperative outcomes were collected and compared in all the patients. Prosperity-score matched (PSM) methods was used to balance baseline characteristics. Results: There was no significant difference in age (P=0.246), gender (P=0.572), tumor location (P=0.333), pathological risk classification (P=0.543), Ki-67 index (P=0.212) and follow-up time (P=0.831) in ER and LAP group. However, significance difference was found in times to liquid diet intake (4.45±1.2 vs 5.40±1.5 days, P= 0.013), and hospital stays (7.72±1.1 vs 10.01±1.3 days, P<0.001). During the follow-up period, there was 1 recurrence in the ER group vs. 2 recurrences in the LAP group. After PSM, the tumor size was balanced between the 2 groups with 49 patients in each group. The times to liquid diet intake (4.18±1.3 vs 5.16±1.6 days, P= 0.042), and hospital stays days (7.12±1.1 vs 9.94±1.3, P<0.0001) were still shorted in ER group. Conclusions: ER is associated with a quick postoperative recovery than LAP. ER could be an alternative approach for gastric GISTs (2-5cm) . However, the long-term follow-up outcomes are still unclear and random control trials are needed.